Portuguese Fertility: Southern or Eastern European Behaviour? - Mendes, Maria Filomena (2014)
When we establish a comparison between period fertility rates in 2000-2005 and 2006- 2010, in the European context, Portugal is the only country presenting a negative evolution of period fertility. Furthermore, Portugal is, in Europe, one of the countries that is still not recovering at the cohort fertility level. The main objective of this work is to contextualize the Portuguese fertility and to understand if (and why) period fertility behaviour and its context are analogous to the countries of southern or eastern Europe. Additionally, the aim of this study is also to understand if the economic and labour market indicators reflect in the same direction for the two European regions in analysis.